Clinico-epidemiological and vaccination profile of patients attending flu clinic of a tertiary health care institution in Eastern India during the third wave of COVID-19 pandemic - Singh, CM; Chaudhary, Neha; Naik, Bijaya Nanda; Rao, Rajath; Pandey, Sanjay; Kumar Nirala, Santosh; Ranjan, Alok; Prasad, Santosh (Publishing Office of the University of Rzeszow, 2022)
Introduction and aim. With the third wave of COVID-19 hitting the country, there is an urgent need to systematically document the clinical-epidemiological and vaccination details of the patients to formulate evidence-based decisions. So, this study was planned to describe the profile of patients attending the flu clinic of a tertiary care hospital in eastern India. Material and methods. This hospital-based cross-sectional study was done for 6 weeks (Jan-Feb 2022) among 623 patients using a pre-tested, structured questionnaire related to COVID-19. An unadjusted odds ratio was calculated and statistical significance was attributed to a p-value <0.05. Results. Out of 623 patients, almost 90% of the patients were vaccinated against COVID-19 with at least one dose of any vaccine. Cough (57.8%) was the most common complaint. Patients aged > 60 years and those having one or more than one comorbidity suffered from moderate-severe COVID-19 infection when compared to their counterparts (p<0.001). Also, 2.1% of fully vaccinated, 3.8% of one dose vaccinated and 10.9% of unvaccinated patients suffered from moderate-severe COVID-19. Conclusion. During the third wave of the COVID-19 pandemic, a smaller number of elderlies compared to the previous two waves were affected indicating age shifting. The severity of COVID-19 was less among vaccinated individuals compared to unvaccinated highlighting the importance of COVID-19 vaccination.
This study was approved by Institute Ethics Committee, AIIMS Patna (Ref: AIIMS/Pat/IEC/2022/859). We adhered to the principles of ethics thereafter throughout the study.
Keywords: COVID-19; epidemiology; mutation; pandemic; SARS-CoV-2; vaccination